Effect of Artificial Saliva Contamination on Bond Strength to Pulp Chamber Dentin - Ară, Hale; Dönmez, Nazmiye; Belli, Sema (European Journal of Dentistry, 2008)
Objectives: The purpose of this in vitro study was to evaluate the effect of artificial saliva contamination on microtensile bond strength to pulp chamber dentin.Methods: Clearfil SE Bond (SEB) (Kuraray, JAPAN) adhesive system and Clearfil Photo Posterior (CPP) (Kuraray, JAPAN) composite resin were used. Twenty extracted caries-free human molar teeth were randomly distributed into four groups. Apart from a control group without contamination (Group 1), primed dentin surfaces were contaminated with artificial saliva (10 s), rinsed, dried, reprimed and bonded (Group 2), coated with adhesive, contaminated with artificial saliva, rinsed, dried, bonding procedures were repeated (Group 3), coated with adhesive, light cured, contaminated with saliva, rinsed, dried, treated with SE primer (SEP) and SEB (Group 4).After 24 hrs, the teeth were prepared for microtensile bond testing and tensile bond strength was measured (1mm/min). The data was calculated as MPa and analyzed using one-way ANOVA and Duncan test (P<.05).Results: The results indicated that Group 2 showed lowest bond strength when compared to the others (P<.05). No statistically significant difference was found between Groups 3 and 4 (P>.05).Conclusions: It was concluded that contamination during priming procedure has a negative effect on bond strength (P<.05). Although contamination of the uncured adhesive was not critical in this study (P>.05) any kind of contamination of the bonding area should, in principle, be avoided. (Eur J Dent 2008;2:86-90)
Keywords: Saliva contamination; Self-etch adhesive; Bond strength